The influence of temperature on set voltage for different high resistance state in 1T1R devices. (1st February 2019) - Tan, Yung-Fang; Su, Yu-Ting; Chen, Min-Chen; Chang, Ting-Chang; Tsai, Tsung-Ming; Tseng, Yi-Ting; Yang, Chih-Cheng; Zheng, Hao-Xuan; Chen, Wen-Chung; Lin, Chun-Chu; Ma, Xiao-Hua; Hao, Yue; et al.
Abstract: HfO2 -based 1T1R is researched in this paper. The on–off ratio is an important electrical characteristic of RRAM, with a larger on–off ratio being preferable. However, temperature also affects the set process when operating RRAM. This study finds that the set process has different sensitivities to temperature at different high resistance states (HRSs). The set voltage of the higher HRS decreases with increasing temperature, while in the lower HRS, set voltage is independent of temperature. From the result, the lower HRS is better for RRAM because it is stable at different temperatures.